Insights into microphysical and optical properties of typical mineral dust within urban snowpack via wet and dry deposition in Changchun, northeastern China - T. Shi; T. Shi; T. Shi; J. Wang; J. Wang; D. Zhang; J. Cui; Z. Wang; Y. Zhou; W. Pu; Y. Bai; Y. Bai; et al. (The Cryosphere)
This study presents the first compositional analysis of dust in snowpack from a typical Chinese industrial city utilizing computer-controlled scanning electron microscope combined with k-means cluster analysis and manual experience. The dust is predominantly composed of kaolinite-like (36 %), chlorite-like (19 %), quartz-like (15 %), illite-like (14 %), hematite-like (5 %), and clay-mineral-like (4 %) particles, with minor contributions from other components. It was also found that the size distribution and aspect ratio of the dust did not undergo significant changes during dry and wet deposition, but they exhibited great variability among the different mineral composition groups. Subsequently, these observed microphysical parameters were used to constrain the optical absorption of dust, and the results showed that under low (high) snow grain size scenarios, the albedo reductions caused by dust concentrations of 1, 10, and 100 ppm in snow were 0.007 (0.022), 0.028 (0.084), and 0.099 (0.257), respectively. These results emphasize the importance of dust composition and size distribution characteristics in constraining snowpack light absorption and radiation processes.